AIR INFLATED STAGE ROOF STRUCTURE WITH INDEPENDENT ENERGY FOR SMES EXHIBITION (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Applied Research with objects of the SME Exhibition Stage in the form of portable stage buildings with inflatable structure roofs using PVC Tarpaulin fabric material. These facilities can be built, dismantled and moved to other locations easily, safely, quickly and lightly with independent energy sources (photovoltaic solar energy systems). The research objective is to develop stage facilities as a means of exhibiting SME products that fulfill aesthetic aspects, strength, speed, effectiveness, comfort and energy saving so as to encourage the development of creative economy SMEs. The research method used the Experimental Method and Action Research, beginning with the development of design, manufacture and testing of portable stage models with pneumatic air inflated stage roofs of Independent Energy, including: (1) speed test of the manufacture, transport, assembly, installation, dismantling of pneumatic air inflated structures and solar energy modules, (2) strength testing of Air Inflated materials (3) thermal comfort tests under the roof of the stage of Air Inflated pneumatic structures, (4) testing the effectiveness of using photovoltaic solar energy to drive inflatable stage roof blowers. The tests were carried out at the University of Merdeka Malang Lab and Field Tests in Malang City and Regency, proved to provide reliable and satisfying results, including: a) speed of installation and demolition installations (23 minutes portable stage, 6 minutes inflatable roof, solar panel installation 15 minutes) , b) the required air pressure is only 0.7 psi to set up an inflatable roof, c) the tensile strength of PVC tarpaulin material reaches 312 kg / cm2, d) 4 solar panels each with a capacity of 100 wp with energy storage in the form of a 100 AH battery 12 V and 1000 W converter in bright conditions produce a minimum of 11.6 Amp, 18.8 V can provide energy needs to drive inflatable stage roof blowers and portable sound systems, and f) comfort under the inflatable roof maximum temperature of 350C. The portable stage and the practical and fast-build inflatable stage roof are expected to become a prototype of stage facilities for SME Exhibition on a national scale.